2017
DOI: 10.1038/srep40737
|View full text |Cite
|
Sign up to set email alerts
|

Individualised multiplexed circulating tumour DNA assays for monitoring of tumour presence in patients after colorectal cancer surgery

Abstract: Circulating tumour DNA (ctDNA) has the potential to be a specific biomarker for the monitoring of tumours in patients with colorectal cancer (CRC). Here, our aim was to develop a personalised surveillance strategy to monitor the clinical course of CRC after surgery. We developed patient-specific ctDNA assays based on multiplexed detection of somatic mutations identified from patient primary tumours, and applied them to detect ctDNA in 44 CRC patients, analysing a total of 260 plasma samples. We found that ctDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…Noninvasive biopsy provides a valuable way to monitor tumor treatment efficacy . As shown in Supporting Information Figure S5A, the amount of unanticipated points became less along treatment course from cfDNA1 to cfDNA3, indicating the overall pattern of cfDNA approached the reference genome, that is, the pattern of WBC, as treatment progressed.…”
Section: Resultsmentioning
confidence: 99%
“…Noninvasive biopsy provides a valuable way to monitor tumor treatment efficacy . As shown in Supporting Information Figure S5A, the amount of unanticipated points became less along treatment course from cfDNA1 to cfDNA3, indicating the overall pattern of cfDNA approached the reference genome, that is, the pattern of WBC, as treatment progressed.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies focused on the comparison of pre-and postsurgical ctDNA reported decreased frequency of mutated variants after tumor resection in various cancers. Sun et al 37 demonstrated that the postoperative mutation frequency decreased compared with preoperative ctDNA variants matched those were detected in tumor tissue in the majority of patients; Chan et al 38 detected tumorassociated copy number aberrations that disappeared almost completely in plasma samples 1 week after tumor removal; Harris et al 24 found somatic chromosomal rearrangements in plasma samples after surgery in only patients with detectable disease, while no aberrations in those without continued disease; and Ng et al 39 observed almost no primary tumor-specific mutations in the postsurgical ctDNA that were present in the plasma samples before surgery in colorectal cancer patients. Further researchers also demonstrated that the frequency of preoperative mutated variants identified in lung cancer by NGS approaches was significantly decreased or completely disappeared within 2 days of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found a positive correlation between tumor burden and cfDNA baseline in NSCLC (Fig 1). Although the tumor-derived fraction of these total cfDNA (ctDNA) has been widely investigated as a prognostic biomarker in various cancer types including breast, colon and lung cancer [18,[44][45][46], the main challenges are low amount of ctDNA, detection cost and reproducibility limitations. For example, some typical difficulties of NGS application in this scenario include inadequate analytical sensitivity and specificity, such as detection limit of low allelic frequencies, and sequencing false positive [43,47].…”
Section: Discussionmentioning
confidence: 99%